2020
DOI: 10.3390/en13040889
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pig Manure and Corn Straw Generated Biogas and Methane Enriched Biogas on Performance and Emission Characteristics of Dual Fuel Diesel Engines

Abstract: In recent years, due to stringent emission regulations vehicle manufacturers have been compelled to cut down noxious pollutants released from diesel engines. Different alternative solutions have been recommended to achieve this challenging task. One of these alternative solutions is the utilization of biogas in addition to the use of liquid diesel. In this regard, the current study investigates the combustion characteristics and exhaust emissions of a turbocharged, direct injection, diesel engine operating at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…The adaptation of IC engines to combustion of gaseous fuels may become a contemporary scientific trend as to the use of biogas [90][91][92]. Biogas obtained from the decomposition of, e.g., sewage [93], organic municipal waste [94,95], animal faeces [96], agricultural and food industry waste [97,98] and plant materials [96,97,99], can be used by plants processing these materials to propel their machinery and equipment [100,101]. Biogas is a mixture of gases characterized by a varied composition, but it can be purified to bio-methane and then meet the quality standards of natural gas [102].…”
Section: Discussionmentioning
confidence: 99%
“…The adaptation of IC engines to combustion of gaseous fuels may become a contemporary scientific trend as to the use of biogas [90][91][92]. Biogas obtained from the decomposition of, e.g., sewage [93], organic municipal waste [94,95], animal faeces [96], agricultural and food industry waste [97,98] and plant materials [96,97,99], can be used by plants processing these materials to propel their machinery and equipment [100,101]. Biogas is a mixture of gases characterized by a varied composition, but it can be purified to bio-methane and then meet the quality standards of natural gas [102].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, its effective passage area must be small enough, and this feature is called permeability. The turbine discharge pressure is obtained from summing up the reference pressure of the inlet gas mixture to the compressor (p 0 ) and the outlet back-pressure of exhaust gases (p bp ), see Equation (36). Equation (37) represents the turbine expansion ratio (r expansion ):…”
Section: Turbochargingmentioning
confidence: 99%
“…This can be attained when biogas is used as fuel due to its good detonation resistance [35]. The use of biogas using a dual-fuel turbocharged engine was evaluated by Ahmed et al [36]. These authors concluded that the presence of biogas did not adversely affect brake thermal efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The results show a remarkable increase in maximum performance parameters with increased engine speed and equivalence ratio. Salman Abdu et al [10] have shown using GT-Power software that the use of the dual-fuel mode is important for reducing emissions and improving the performance of the turbocharged direct injection diesel engine.…”
Section: Introductionmentioning
confidence: 99%